Strategi Kooperative Learning dalam Pembelajaran Al-Qur’an Hadits Untuk Meningkatkan Motivasi Belajar Siswa Kelas V di Mi Hidayatul Husna - Lusiana, Yusria; Yunita, Vera Dina; Sirriyah, Mia Mukhlisiyyatus (Lembaga Yasin AlSys, 2021)
This study aims to This study aims to increase the learning motivation of Class V students of MI Hidayatul Husna in the village of Krasak Pecangaan Jepara in the 2021/2022 academic year in the Qur'an Hadith Subject through the Cooperative Learning model. This study uses a one-cycle type of research which includes the following stages: 1) planning, 2) implementation, 3) observation, 4) reflection. The action research was carried out in one cycle of 36 students, there were 28 students or 78% achieving the predetermined completeness while 8 students or 22% had not achieved completeness. The highest score obtained is 93 while the lowest score is 65. The average student learning outcome is 82. Based on the actions taken, it can be concluded that the application of the cooperative learning model can increase the learning motivation of the fifth grade students of MI Hidayatul Husna Jepara in the 2021/2022 academic year in the Qur'an subject. 'an Hadith.